PENGARUH HARGA DAN FASILITAS TERHADAP KEPUTUSAN BERKUNJUNG WISATA PANTAI PASIR PUTIH PARPAREAN KABUPATEN TOBA - Retno S. Manurung; Nurul Wardani Lubis; Diana Hasyim (Universitas Methodist Indonesia, 2023)
This study aims to determine the effect of price and facilities on the decision to visit the Parparean White Sand Beach Tourism in Toba Regency. This study used quantitative methods and determined the sample using simple random sampling method with a total sample of 100 respondents. Data collection techniques in this study were carried out by distributing questionnaires with a Likert scale and statistically processed using multiple regression analysis with the help of the SPSS 21.0 calculator for windows. Hypothesis testing uses the f test, t test and the coefficient of determination previously the data has been tested using the validity test, reliability test and classic assumption test. The results of this study indicate that partially the price and facilities have a positive effect on the decision to visit Pasir Putih Parparean Beach, Toba Regency. The results of the study also show that prices and facilities simultaneously influence visiting decisions. This is evidenced by the results of the value of Fcount > Ftable = 71.481 > 3.09 and a significance level of 0.000 <0.05. The coefficient of determination test shows a value of 0.596 or 59.6% which means price and facilities have an influence of 40.4% on the decision to visit while the rest is influenced by other variables.